Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Konsumen Dan Loyalitas Konsumen Kopi Kenangan - Indah Wulan Sari; Lia Amalia (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Service quality is one of the main things that are considered in the company. Customer assessment of service quality is very important for service providers, because it affects the company's performance and position in the market. Service quality as a result of the perception of the comparison between customer expectations with the actual performance of services. In other words, there are two main factors that affect service quality, namely expected service (expected experience) and perceived service (service received). Meanwhile, the total quality of a service consists of 3 main components, namely: technical quality (consisting of: search quality, experience quality, credence quality), functional quality, and corporate image. This study aims to determine the effect of Service Quality and Brand Image on Consumer Satisfaction and Consumer Loyalty. This type of research uses quantitative as many as 170 respondents. With the analysis technique in this study using SEM analysis. The results of this study partially show that the service quality variable has a positive effect on consumer satisfaction. Brand Image has no effect on Consumer Satisfaction. Service Quality has no effect on Consumer Loyalty. Brand image has no effect on Consumer Loyalty. Consumer Satisfaction has no effect on Consumer Loyalty.